In Vitro Activity of Garenoxacin against Streptococcus pneumoniae Mutants with Characterized Resistance Mechanisms - Yamamoto, Kazuko (American Society for Microbiology (ASM), 2009)
We evaluated the potency of garenoxacin in selecting resistant Streptococcus pneumoniae mutants by determining its mutant prevention concentration, using strains with and without topoisomerase gene mutations, and compared its potency to that of other quinolones. Garenoxacin had a significantly greater potency against pneumococci, including strains containing topoisomerase mutations. Genetic analysis of the S. pneumoniae mutants created by garenoxacin revealed that the gyrA gene was a primary target of garenoxacin.